Comprehensive Analysis of Data Security Threats in the Public Sector - Putri, Aulia Kartika; Nurmandi, Achmad; Younus, Muhammad; Lawelai, Herman; Suardi, Wahdania; Zainudin, Arif (Universitas Sultan Ageng Tirtayasa, 2025)
This research addresses the topic of data security threats in the public sector, which has become a major concern along with the digitization of public services and the increasing incidence of cyberattacks. The aim is to analyze the main threats, including human error, internal threats, as well as external attacks such as ransomware and phishing, that can compromise the privacy and security of public data. Using a qualitative approach and bibliometric analysis, the study included a review of 192 Scopus articles from 2014 to 2024 and VOSviewer as a data processing tool for the data generated. The results indicate that data security in the public sector requires a multidisciplinary approach, including innovative technologies such as AI and blockchain, stronger data privacy regulations, and effective incident response mechanisms. The research concludes that global collaboration and an integrated approach are essential to address the increasingly complex challenges of data security while ensuring safe and reliable public services.